The European image of God and man : a contribution to the debate on human rights - Günther, Hans Christian.; Robiglio, Andrea A., 1972- (Studies on the Interaction of Art, Thought and Power, 2010)
The present volumes unites papers which explore the European image of god and man as the unquestioned basis of the concept which determines what western society defines as human rights and puts it in an intercultural context by comparative essays on chinese, islamic and buddhist thinking. The volume covers issues which range from classical antiquity until contemporary philosophy and science.